Kebocoran Data di Media Sosial: Analisis Pola dan Strategi Pencegahannya - Lesmana, Rendy; Nasution, Muhammad Irwan Padli (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Social media has become the main space for digital interaction used by billions of people around the world. Behind its benefits in accelerating communication and dissemination of information, there are serious threats to the security of users’ personal data. Data leaks on social media have become an increasingly frequent phenomenon and have negative impacts, such as identity theft, online fraud, and privacy violations. This study aims to analyze common patterns of data leaks that appear on various social media platforms and to develop preventive strategies that can be applied to minimize these risks. Through a qualitative approach with literature studies and case analysis, it was found that data leaks are often caused by a combination of weak platform security systems, low user awareness of the importance of privacy, and data collection and processing practices by third parties without transparency. This study suggests several mitigation strategies, including increasing digital literacy for users, improving more accountable privacy policies, implementing advanced security technologies such as encryption and double authentication, and strengthening data protection regulations by authorized authorities. Thus, the results of this study are expected to provide a real contribution in creating a safer, more transparent, and more responsible digital ecosystem for all stakeholders, including users, platform developers, and the government.